Transient Unidirectional Solidification, Microstructure and Intermetallics in Sn-Ni Alloys - Cruz,Clarissa Barros da (2018)
The present research work examines the microstructural arrangements formed during the transient solidification of eutectic Sn-0.2wt.%Ni and hypereutectic Sn-0.5wt.%Ni alloys. Also, it examines their respective correlations with solidification thermal parameters: eutectic growth rate (VE) and eutectic cooling rate (ṪE); length scales of matrix and eutectic phases: microstructural spacings and the corresponding tensile properties: ductility and strength. Both alloys were directionally solidified upwards under unsteady-state regime, and characterized by optical and scanning electron microscopy. Concerning the hypereutectic Sn-0.5wt.%Ni, the increase in Ni content is shown to influence both thermal behavior and cellular spacing (λC). The NiSn4 intermetallics is present in the eutectic mixture of both alloys, whilst in the Sn-0.5wt.%Ni alloy the primary phase has been identified by SEM-EDS as the Ni3Sn4 intermetallics. A β-Sn morphological cellular/dendritic transition occurs in the 0.2wt.%Ni eutectic alloy for ṪE> 1.2K/s. Despite that, regular cells in the hypereutectic alloy (0.5wt.%Ni) turns into plate-like cells for ṪE> 1.4K/s. If considered a reference cellular spacing about 20μm (i.e.,λ(c-1/2=0.22), the samples associated with the Sn-0.5wt.%Ni alloy are shown to be associated with higher tensile strengths, but much lower ductility as compared with the corresponding results of the eutectic alloy.